2018
DOI: 10.1002/advs.201800287
|View full text |Cite
|
Sign up to set email alerts
|

In Situ One‐Pot Synthesis of MOF–Polydopamine Hybrid Nanogels with Enhanced Photothermal Effect for Targeted Cancer Therapy

Abstract: Herein, a simple one‐pot way is designed to prepare a type of multifunctional metal–organic framework (MOF)‐based hybrid nanogels by in situ hybridization of dopamine monomer in the skeleton of MnCo. The resultant hybrid nanoparticles (named as MCP) show enhanced photothermal conversion efficiency in comparison with pure polydopamine or MnCo nanoparticles (NPs) synthesized under a similar method and, therefore, show great potential for photothermal therapy (PTT) in vivo. The MCP NPs are expected to possess T 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 56 publications
(43 reference statements)
0
62
0
1
Order By: Relevance
“…Figure a illustrates the stepwise synthesis and surface modification of MCOPP NE for the O 2 generation and enhanced 1 O 2 production. First, the Mn 3 [Co(CN) 6 ] 2 MOFs were fabricated using a co‐precipitation method . Transmission electron microscopy (TEM) images reveal that the as‐prepared MOF nanoparticles had a cubic morphology and were uniformly dispersed with an average diameter of 75 nm (Figure S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Figure a illustrates the stepwise synthesis and surface modification of MCOPP NE for the O 2 generation and enhanced 1 O 2 production. First, the Mn 3 [Co(CN) 6 ] 2 MOFs were fabricated using a co‐precipitation method . Transmission electron microscopy (TEM) images reveal that the as‐prepared MOF nanoparticles had a cubic morphology and were uniformly dispersed with an average diameter of 75 nm (Figure S1, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…It was also reported that noble metal nanoparticles such as Ru, Pt and Au nanoparticles have catalase-like nanozyme activities [40][41][42] . In addition, the polarizable π-electron cloud of [Co(CN) 6 ] may have a certain affinity to cargos with conjugated structures 43 . Thus, during organic linker-metal coordination process, various bioactive molecules could be conveniently encapsulated, indicating that the metal-organic coordination might be an efficient approach for incorporating single-atom catalytic active sites and therapeutic agents in the assembled materials.…”
mentioning
confidence: 99%
“…Moreover, a zinc (Zn)-based MOF could be concocted in a modified dimensional structure for the ramification of better adsorption-reduction capacity. It is noteworthy that the integration of improved ligand-to-metal synergy achieves better photothermal resilience; this aspect not only increases the recyclability of ordinary MOFs' photocatalysts but also critical determinant characteristics for PS design [190]. To elucidate this aspect, in 2018, Ye et al studied ultrathin two-dimensional Zn-MOF [Zn porphyrin], based on TCPP ligand, nanosheet with BET surface area of 445 m 2 •g −1 and CO 2 adsorption potential of 103.8 cm 3 •g −1 .…”
Section: Zn-based Mofsmentioning
confidence: 99%